Ivabradine: Just another New Pharmacological Option for Heart Rate Control? - Perez Riera, Andres Ricardo; Abreu, Luiz Carlos de; Valenti, Vitor Engrácia; Fonseca, Fernando A. L.; Ferreira, Marcelo; Vanderlei, Luiz Carlos Marques [UNESP]; Ferreira Filho, Celso; Monteiro, Carlos B. de Mello; Rolim Neto, Modesto Leite; Rodrigues, Luciano M. R.; Ferreira, Celso (OMICS International, 2011)
Ivabradine (IVB) is a heart rate lowering agent that acts via selective inhibition of the pacemaker funny current in sinoatrial nodal P cells, thus, reducing heart rate at rest and during exercise with minimal effect on myocardial contractility, blood pressure, and intracardiac conduction. IVB exerts no effect on external respiratory function parameters and it may also play a role in patients with concurrent chronic obstructive pulmonary disease. This property constitutes an important advantage over β-blockers. IVB acts by reducing the heart rate in a mechanism different from β-blockers, calcium channel blockers or late sodium channel blockers, three commonly prescribed antianginal drugs. As clinical trials have shown, it is remarkably well-tolerated and offers an alternative for patients who cannot take β-blockers. The combination of IVB and atenolol at commonly used doses in patients with chronic stable angina produced additional efficacy with no untoward effect on safety or tolerability. Additionally, side effects are rare and largely limited to a luminous phenomenon or phosphenes. This sensation is thought to be due to a block of Ih in the retina, a current very similar to cardiac If channels. IVB is contraindicated in patients with sick sinus syndrome or sinus node dysfunction and in patients taking hepatic inhibitors of Cytochrome P450 family 3, subfamily A, polypeptide 4 (abbreviated CYP3A4), with exception of omeprazole or lansoprazole. This review briefly summarizes the main studies regarding this drug.